Reconstruction Of The Protection Of Constitutional Rights Of Political Parties In The Presidential Threshold System - Sukma Aristya; Elok Puri Maharani, Andina (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The presidential threshold is considered to have no normative problems, but when viewed in practice, there are substantive problems. This is because the Presidential Threshold is the nomination threshold as stipulated in Article 222 of Law Number 7 Year 2017 concerning General Elections. This raises big questions about the General Election as a means of organizing democracy, because parties that do not have the number of seats as mentioned cannot propose a pair of candidates for President and Vice President so that it has the potential to limit democratic rights while in the 1945 Constitution of the Republic of Indonesia does not provide restrictions on each political party to propose a pair of candidates for President and Vice President as contained in Article 6A paragraph (2) of the 1945 Constitution of the Republic of Indonesia.